Looking for stability: Experiences of rehabilitation for Congolese survivors of torture in Athens and the role of the Congolese community in their support - Psyrraki, Maria-Angeliki; Venables, Emilie; Eleftherakos, Christos; Severy, Nathalie; Barry, Declan; Gionakis, Nikos; Episkopou, Maria; Komita, Aikaterini; De Maio, Gianfranco (Torture Journal, 2021)
Introduction: On-going conflict and political instability in the Democratic Republic of Congo (DRC) has led to increasing numbers of people fleeing their country for Europe. Many need rehabilitation services upon arrival in Greece after experiencing torture in DRC. The scarcity of state resources and the limited capacity of non-governmental organisations to assist survivors of torture means many needs remain unmet. This study explored the experiences of rehabilitation for male Congolese survivors of torture living in Athens, as well as the potential role of the wider Congolese community in Athens in supporting rehabilitation. Methods: This qualitative study included in-depth interviews with survivors of torture attending a rehabilitation clinic and key informant interviews with representatives of the wider Congolese community in Athens. Data was thematically analysed to construct and develop codes and themes. Results: 19 survivors and 10 key informants were interviewed. For many survivors, rehabilitation was an unclear concept. Despite the appreciation for services received at the clinic and the amelioration of physical and psychological symptoms, survivors felt rehabilitation was incomplete as it did not meet their accommodation needs nor provide stability through granting refugee status. Survivors were wary of trusting other Congolese people after experiencing torture and did not always associate themselves with the local Congolese community. The role of local Congolese leaders and organisations was not seen as replacing the clinical element of rehabilitation but aiding in practical issues such as information sharing and integration, especially in partnership with other organisations. Discussion: Systemic shortcomings in Greece, including poor access to accommodation and insecure asylum status, impeded processes of rehabilitation. Many participants found themselves navigating an unstable and unpredictable landscape in their journey towards “feeling whole again.” The role of the wider Congolese community in Athens in supporting rehabilitation remains complex and a lack of trust threatens social cohesion. Nonetheless, the willingness of the community to be more proactive should not be ignored by organisations and policy-makers.